Quantum magnetotransport in a higly correlated two-dimensional electron liquid on a superfluid helium surface - Monarkha, Yu.P.; Shirahama, K.; Kono, K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
The theoretical concept of the inelastic quantum magnetotransport of highly correlated surface electrons on superfluid helium is presented. The low-temperature magnetoconductivity data are obtained from the damping of the edge magnetoplasmons. It is shown that the temperature and magnetic field dependences of the magnetoconductivity can be perfectly described by the inelastic many-electron theory as the interplay of two kinds of Landau level broadening produced by scatterers and by mutual Coulomb interaction.